ELECTRICAL, OPTICAL, AND CHEMICAL PROPERTIES OF GRAPHENE THIN FILMS FABRICATED BY VACUUM FILTRATION TECHNIQUE - Haji, Shivan H.; Kochary, Faris A.; Ahmed, Sabah M. (Science Journal of University of Zakho, 2024)
There has been considerable interest in graphene as a transparent electrode material because of its extraordinary features, such as high optical transmittance, high electrical conductivity, excellent thermal conductivity, exceptional mechanical strength, and remarkable electrochemical capacity. In addition, transparent conductors’ graphene thin films have been considered a promising candidate to replace currently utilized indium tin oxide films, which are unlikely to meet future demands because of their rising cost. In this study, a vacuum filtration process along with isopropyl alcohol (IPA)-assisted with direct transfer (IDT) technique is used to prepare wide-area highly conductive graphene thin films on different substrates including (glass, and PET). The graphene thin films’ optical, structural, and electrical properties are studied. The graphene sheets are deposited homogeneously on the substrate, and the distribution of small graphene sheets is observed in SEM images. XPS analysis revealed that the amount of oxygen in graphene decreases significantly with annealing at 500°C and treated with HNO3. Furthermore, the graphene transparent conductive films prepared by the adjusted vacuum filtration method show low sheet resistances of 12.2, 1.41, 1.18, and 0.8 kΩ/sq with transmittances of 81%, 70%, 64.3%, and 46.4% respectively after being annealing at 500°C and treated with HNO3.